Pengendali Derau Secara Aktif Menggunakan ANFIS (Active Noise Controller Using ANFIS) - Nusantoro, Goegoes Dwi (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2008)
ANFIS Controller used for the reduction of noise actively (active noise cancellation, ANC) in a duct, at this research, only use three input and two membership function of every input and also two rule so that totalize the parameter used by 20 parameters, good of premis and also it concequent. While algorithm learn used to update its parameter is on line backpropagation.Pickings got in simulation indicate that the ANFIS controller own the better performance in noise cancellation in all frequency area, good of narrowband and also broadband, compared to by a performance a FIR filter Filterd-X LMS algorithm though with the parameter which must be update slimmer.